Technology Readiness Levels for vaccine and drug development in animal health: From discovery to life cycle management - Arnouts, Sven; Brown, Scott; de Arriba, M. Luisa; Donabedian, Michael; Charlier, Johannes (Frontiers in Veterinary Science, 2022)
Public research and innovation initiatives in animal health aim to deliver key knowledge, services and products that improve the control of animal infectious diseases and animal welfare to deliver on global challenges including public health threats, environmental concerns and food security. The Technology Readiness Level (TRL) is a popular innovation policy instrument to monitor the maturity of upcoming new technologies in publicly funded research projects. However, while general definition of the 9 levels on the TRL-scale enable uniform discussions of technical maturity across different types of technology, these definitions are very generic which hampers concrete interpretation and application. Here, we aligned innovation pipeline stages as used in the animal health industry for the development of new vaccines or drugs with the TRL scale, resulting in TRL for animal health (TRLAH). This more bespoke scale can help to rationally allocate funding for animal health research from basic to applied research, map innovation processes, monitor progress and develop realistic progress expectations across the time span of a research and innovation project. The TRLAH thus become an interesting instrument to enhance the translation of public research results into industrial and societal innovation and foster public-private partnerships in animal health.